Molecular differences between human and experimental pancreaticobiliary diversion-induced rat pancreatic neoplasia. Issue 5 (May 1991) - Hall, P A; Lemoine, N R; Murphy, G; Dowling, R H
Abstract : A series of molecular changes are now known to be seen in human pancreatic neoplasia, including the very frequent mutational activation of Kirsten ras oncogene at codon 12, overexpression of the epidermal growth factor receptor, and abnormalities of c-erbB-2 expression. In order to determine whether similar changes can be seen in animal models of pancreatic cancer a molecular analysis of tumours induced in rats by pancreaticobiliary diversion was performed. The polymerase chain reaction was used to amplify portions of the rat Kirsten ras gene and sequence specific oligonucleotide hybridisation was used to define whether sequences were wild type or mutant. No evidence of mutation was found in the Kirsten ras gene at codons 12 or 61, where activating mutations are known to occur. In addition immunohistochemical methods were used to investigate expression of c-erB-2 and the epidermal growth factor receptor but no evidence of abnormal expression was found. We conclude that there are major molecular differences between human and experimental rat pancreatic cancer.